Exploring Students’ Engagement toward Indirect Corrective Feedback in Writing a Report Text - Yudhia, Septiara Dwi; Aminin, Zainul (Jurnal Bahasa Inggris, 2022)
Indirect corrective feedback is the type of feedback that requires the students to understand the teacher’s signs, and they should understand the feedback independently. This study aims to determine the process of students’ three aspects of engagement involve affective, behavior, and cognitive engagement. It is significant to discover the engagement of students concerning indirect corrective feedback to explore how the teacher and students’ relationship happened. Specifically, this study mainly focused on one class of vocational high school students in multimedia class grade X. Writing a report text was the activity occurring in the study. Furthermore, this study used qualitative research to explore the students’ process in a writing activity. This study had two instruments documentation of students’ drafts and semi-structured interview. The study found that students were affectively, behaviorally, and cognitively engaged in the teacher’s indirect corrective feedback. Although, a few students had different perspectives related to the implemented feedback.